Suicide, other externally caused injuries and cardiovascular death following a cancer diagnosis: study protocol for a nationwide population-based study in Japan (J-SUPPORT 1902) - Tatsuo Akechi; Yosuke Uchitomi; Saki Harashima; Maiko Fujimori; Tomohiro Matsuda; Kumiko Saika; Takaaki Hasegawa; Keisuke Inoue; Kazuhiro Yoshiuchi; Isao Miyashiro; Yutaka J Matsuoka (BMJ Open)
Introduction A growing body of literature has demonstrated that cancer patients have a higher risk of suicide and cardiovascular mortality compared with the general population, especially immediately after a cancer diagnosis. Using data from the National Cancer Registry in Japan launched in January 2016, we will conduct the first nationwide population-based study in Japan to compare incidence of death by suicide, other externally caused injuries (ECIs) and cardiovascular disease following a cancer diagnosis with that of the general population in Japan. We will also aim to identify the patient subgroups and time periods associated with particularly high risk.Methods and analysis Our study subjects will consist of cancer cases diagnosed between 1 January 2016 and 31 December 2016 in Japan and they will be observed until 31 December 2018. We will calculate standardised mortality ratios (SMRs) and excess absolute risks (EARs) for suicide, other ECIs and cardiovascular death compared with the general population in Japan, after adjustment for sex, age and prefecture. SMRs and EARs will be calculated separately in relation to a number of factors: sex; age at diagnosis; time since cancer diagnosis; prefecture of residence at diagnosis; primary tumour site; behaviour code of tumour; extension of tumour; whether definitive surgery of the primary site was performed; and presence/absence of multiple primary tumours.Ethics and dissemination The study protocol was approved by the institutional review board and ethics committee of the National Cancer Center Japan and Nagoya City University Graduate School of Medical Sciences. The findings will be disseminated through peer-reviewed publications and conference presentations.Trial registration number UMIN000035118; Pre-results.